PENGEMBANGAN MEDIA KARTU KATA BERGAMBAR BERBASIS POWERPOINT UNTUK PERKEMBANGAN BAHASA ANAK DI TK ISLAM BAKTI 71 SIALANG GAUNG - Aprimadedi; Sri Yunimar Ningsih; Henny Nuryah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by several things that the author found in the intial observations.The purpose of this research is to produce a product in the from of powerpoint-based picture word card media in TK Islamic bakti sialang gaung that is valid,practical,and effective. This type of research is research and development,which uses the ADDIE development model which consists of analysis,design,development,implementation,evaluation stages.The analysis phase includes an analysis of the child’s needs.an analysis of the child’s characteristic.the design stage carried out material and media design.the out practicality tests,and the effectiveness test was carried out at TK Islamic Bakti Sialang Gaung,Koto Baru District,Dharmasraya Regency,and the evaluation stage carried out an assessment of these results,The result of powerpoint-based picture word card media validation assessment on the validaty test by there exprest,material exprest,and linguists with very valid and valid category,practicality test with very practical category,and effectiveness results with the effective category. It can be concluded that the media powerpoint-based picture word card are declared valid,and effective